Inovasi Evaluasi Pembelajaran dalam Kurikulum PAI - Maimunah, Maimunah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The purpose of writing this work is to describe Learning Evaluation Innovations in the PAI Curriculum. This library research research method includes collecting literature related to learning evaluation innovations in the PAI curriculum, literature selection based on inclusion and exclusion criteria, as well as literature analysis to identify patterns, trends and related findings. Data will be collected from academic literature, scientific journals, books and relevant online sources, then analyzed carefully to gain an in-depth understanding of the research topic. The results of this work, namely learning evaluation innovations in the PAI curriculum in public schools and madrasas in Indonesia, are important for overcoming challenges such as time constraints and the lack of integration of religious values ​​in students' lives. Proper evaluation helps identify curriculum strengths and weaknesses and provides recommendations for improvement, while innovation in learning methods needs to be increased to achieve comprehensive and relevant educational goals. In madrasas, PAI curriculum evaluation should include an assessment of student attitudes, knowledge and skills, with special attention to the implementation of innovative learning methods and infrastructure development and teacher quality.